Prevalensi dan Faktor Risiko Penyakit Pedikulosis Kapitis di Sekolah Dasar Negeri Duri Kepa 11, Jakarta Barat - Sabini, Jasmine Harumi; Sari, Monica Puspa; Far-Far, Inggrid Osya (Universitas Kristen Krida Wacana, 2025)
Pediculosis capitis is a head lice disease because it causes discomfort to sufferers in the world. The disease can affect all ages and especially elementary school children. The purpose of this study was to determine the prevalence of pediculosis capitis and risk factors for infestation in children at SDN Duri Kepa 11, West Jakarta. The research method was observational analytic with a cross sectional approach conducted in November 2023. The sample size of the study was 323 samples with a total sampling technique. Head lice examination was carried out visually and using a lice comb. Samples responses were collected through questionnaires. Bivariate data analysis was carried out using SPSS 25. The prevalence of pediculosis capitis in children at SDN Duri Kepa 11 was 23,8%, higher in female students, certain classes and students with housewives. Factors related to pediculosis capitis infestation at SDN Duri Kepa 11 were gender (p value = 0,000), hair shape (p value = 0,004), frequency of hair washing (p value = 0,007) and use of shared combs and towels (p value = 0,000). The prevalence of pediculosis capitis in children aged 7-13 years at SDN Duri Kepa 11, west Jakarta is quite high so that prevention and treatment are needed so that the prevalence can be further reduced.